Analisis Persepsi Karyawan Terhadap Harapan Dan Kenyataan Operasional Berdasarkan Metode Ishikawa Dan Metode Spider Plot Pada Pt. Tata Makmur Bersama Di Sidoarjo - Nurul Qomari; Musriha Musriha; Hendra Hendra (Fakultas Ekonomi Universitas Kadiri, 2022)
This study is to test and analyze employee perceptions/responses to operational expectations and realities in the factors of production based on Ishikawa diagrams/methods and spider plot methods at PT. Prosperity Together in Sidoarjo. The advantages of the field Increasing the ratio as a scale has been described through Cartesian diagrams and Spider Plots with the detection of the farther between expectations and reality being the cause of extreme dissatisfaction felt by employees. For short-term and long-term strategic maps for management, it can be seen in the Cartesian diagram that has been presented by researchers with a priority scale (short term) to improve the Main Priority quadrant. For long-term improvement, company management can use data in the Maintain Achievement and Low Priority quadrant